Women in Physical Education and their Career Development: Current Trends and Issues - Ho, Walter; Rafael, Klaudia; Ahmed, Dilsad; Xie, Jennie Yang Yang (International Sports Studies, 2024)
Participation in physical education (PE) is a fundamental right for every student (UNESCO, 2012). The quality of learning in PE depends on several factors, including access to facilities, learning opportunities, well-designed curricula, and effective teaching by qualified professionals. While PE teaching is a career open to both genders and protected by policies that ensure equal working opportunities, female professionals often face unique challenges in pursuing and advancing in this field. This study examines the career choices of female PE professionals, focusing on the social constraints they encounter and their implications for women pursuing careers in the field. It also investigates gender-specific perceptions of Quality Physical Education (QPE) to identify differences across key dimensions of QPE. This study draws on data from a global survey on QPE conducted between 2020 and 2021. Using a 49-item questionnaire developed by the International Society for Physical Education and Sport (ISCPES) research team, the study engaged 5,680 professionals comprising 2,431 women and 3,249 men. Respondents were primarily from Asia, the Middle East, and Central and South America, with fewer participants from Europe and Africa. This study employed the boundary concept and compromising practice framework to analyse trends in women’s career choices, social and professional challenges, and prospects in PE careers. Findings revealed that both genders exhibited similar attitudes toward QPE development, with no significant differences in the overall score by gender. Nevertheless, women expressed more positive perceptions of QPE at the primary level than men.